Estimativas de Parâmetros Genéticos e variabilidade entre genótipos de maracujazeiro - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Resumo em língua estrangeira: Sour passion fruit (Passiflora edulis) is the most cultivated species of genus Passiflora in Brazilian territory. Native to South America, the fruit has an attractive flavor, being widely consumed all around the world, either in natura or in some processed form. In addition, its plant is used to produce several subproducts derived from the fruit, from the leaves or from the peel, being processed by a variety of industrial branches. This work aimed to evaluate the productive level and the quality of the fruits, to estimate the genetic parameters and predict the genetic variability of ten cultivars and sixteen progenies of sour passion fruit trees grown under the soil and the climate conditions of the Northeast of the Brazilian state of Goiás. The experiment was conducted from March 2020 to February 2021 at the Rural School of the State University of Goiás, Campus Northeast, located in the municipality of Posse. In the study, randomized complete blocks with four replicates, 26 treatments on three plants by parcel were used. In addition to 10 commercial cultivars, 16 families of full-siblings and half-siblings of sour passion fruit obtained through Design I of Comstock and Robinson were evaluated. Those fruits from each treatment per parcel were harvested, labeled, and weighted on a digital scale, leading to a record of the overall production into fruits grouped per parcel and made available for the evaluations. For the evaluation of morphological traits of the fruits, the following descriptors were analyzed: weight (g), length and diameter (mm), peel thickness (mm), seeded pulp weight (mm), and degrees Brix (°Bx). As for the morphological traits of the leaves, the length and the width of the leaf limb (mm), as well as the length of the petiole (mm). The data were using ANOVA and the Scott-Knott mean test, the genetic parameters were estimated using the mean square hope and the prediction of genetic variability was performed by the hierarchical UPGMA method, using the Mahalanobis matrix. Seven variables presented differences, thus detecting the presence of variance between treatments. Fourteen progenies and one cultivar presented the largest fruits, through their LF and DF values, and all accessions were classified as an oval. Nine progenies and five cultivars presented fruit with weight above 120 g, within the requirements for the consumer market. Fourteen progenies and nine cultivars presented values above 11 for ° Brix, remaining within the value required by MAPA. The experiment presented effectively satisfactory, according to the value of the coefficient of variation (CV). The coefficient of genetic variation (CVg) showed results ranging from 4.23% to 28.48%. The known index of variation (IV) values are below unity, which showed influence from the environment to characteristics. Heritability values (h2) ranged from low to medium magnitude, ranging from 15.70 to 67.79%. Using the UPGMA hierarchical grouping method, accesses were distributed into 7 groups. The results of the relative contribution revealed that the characteristic of °Brix was the most responsible for the genetic diversity found in the accessions, contributing 23.45%. The results allowed us to infer that although there is no significant difference in terms of production, for the 26 materials of P. edulis cultivated in the northeast of Goiás, it was possible to identify 14 progenies with fruit quality superior to some commercial cultivars. As they do not present desirable fruit characteristics, progenies 3 and 8 must be withdrawals from the breeding program. Of the 10 cultivars tested, only the cultivar IAC 273 Monte Alegre is not recommended for cultivation in the region. Aiming to increase genetic values and minimize environmental values, all evaluated characteristics demand a more complex improvement method to manage the segregating population.
Keywords: Passiflora edulis; População segregante; Ganho genético; Ganho genético; Delineamento Genético I.; Passiflora edulis; Segregating population; Genetic gain; Productivity; CIENCIAS AGRARIAS::AGRONOMIA